Government Policy Accountability On Implementation Of Cash Direct Assistance Program For Communities Affected By Covid-19 (Case Study in Ende Regency) - Nur Iam Ri'a; Maswar Patuh Priyadi; Titik Mildawati (Neo Journal of economy and social humanities, 2022)
This study aims to find out how to apply direct cash assistance, the principle of accountability of government policies, as well as effective and efficient strategies in implementing cash transfers for communities affected by Covid-19 in villages in Ende Regency. This study uses a qualitative descriptive method with a case study approach. The informants who were used as resource persons in this study consisted of the Head of the PMD Service, the Head of the Village Government Division, the Village Government Sector Staff, and the people who received and did not receive assistance. Data collection techniques through interviews, observation, and documentation. The data analysis technique starts from data reduction, data presentation, and drawing conclusions. The results of the study revealed that the distribution of BLT was carried out from April to December 2020 in nine distributions with a total fund of Rp. 3,600,000/KPM. Accountability of government policies starting from the planning stage to the accountability stage is in accordance with regulations and can be accounted for even though in the planning and implementation stages there are time delays. Effective and efficient strategies in the implementation of BLT consist of regulations, individual tasks, programs, ideal goals that have been implemented quite well although there are still shortcomings in their implementation.